EVALUASI KEBIJAKAN OTORITAS KOMPETEN PANGAN ORGANIK DALAM RANGKA MENDUKUNG PEMBANGUNAN PERTANIAN BERKELANJUTAN DI INDONESIA - Harjito, Harjito (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2012)
The objective of this study is to identify whether the results that want to be achieved by implementing the Ministerâ€™s Decision no 380/2005 and Ministerâ€™s decision no 297/2007 regarding governmentâ€™s policy on organic food authority has been achieved? Methods that has been applied is multi-method, with a consideration that the need for data n data analysis could fulfill the research questions. Policy research is combines a number of different research methodsâ€. This study was 5 at the Ministry of Agriculture, Jakarta, Tasik, Yogyakarta, Sragen, Lombok Barat, Organic Sertification Insitution, and farmers groups. Organic Food Competent Authority has successfully laid down four fundamental aspects for organic farming development in Indonesia namely: policy, standard/ guidance for SNI 6729, human resource development, and accreditation of seven (7) organic certification institution. Currently, there are 15 companies that have successfully obtained organic certification with 13 kinds of commodity.